Leadership communication styles, information sharing and performance among selected supply chain managers of private companies - Maulanin, Rommel E.; Serrano, Ernesto A.; Yango, Antonio R. (Technium Social Sciences Journal, 2023)
This study attempted to determine the leadership communication styles, information sharing and performance among selected supply chain managers of private companies in Laguna. Specifically, it investigated the supply chain managers’ leadership communication style, level of information sharing, and level of performance. Further, the study probed the relationship between the supply chain managers’ leadership communication style and level of information sharing, leadership communication style and level of performance, level of information sharing and level of performance. Finally, it probed the predictive ability of the supply chain managers’ leadership communication style, and level of information sharing, taken singly or in combination, of level of performance. The descriptive-correlational research design was employed in this investigation. The respondents of this study were composed of employees working in the supply chain of selected private companies in Laguna consisting of 100 . The researcher used Raosoft sample size calculator with a 10% margin of error and 90% confidence level to come up with the sample size of 80. The respondents were selected through stratified random sampling technique. The study findings showed that that an average weighted mean of 3.22 revealed the supply chain managers’ leadership communication style was good, an average weighted mean of 3.21 revealed the supply chain managers’ level of information sharing was high , an average weighted mean of 3.21 revealed the supply chain managers’ level of performance was high , there was a significant relationship between the supply chain managers’ leadership communication style along competency (p=0.000), consistency (p=0.000), commitment (p=0.000) and level of information sharing. The probability value of 0.000 was less than the 0.01 significance level. However, no significant relationship was noted between command and control and level of information sharing. The probability value of 0.470 was greater than the 0.05 significance level, there was a significant relationship between the supply chain managers’ leadership communication style along competency (p=0.000), consistency (p=0.000), commitment (p=0.000) and level of performance. The probability value of 0.000 was less than the 0.01 significance level. However, no significant relationship was noted between command and control and level of performance. The probability value of 0.470 was greater than the 0.01 significance level, and there was a significant relationship between the supply chain managers’ level of information sharing and level of performance. The probability values of 0.000 was obtained which was less than 0.01 level of significance. On the other hand, a probability value of 0.000 indicates a high level of prediction of the dependent variable (level of performance). The obtained R square of 0.782 shows that independent variables (supply chain managers’ leadership communication style and level of information sharing) explain the variability of the dependent variable (level of performance). Further, the ANOVA shows that the independent variables the supply chain managers’ leadership communication styles along command/control and competency as well as their level of information sharing statistically significantly predicted the dependent variable level of performance with an F-value of 53.151 and a probability value of 0.000 which is less than the 0.05 significance level. It was concluded in the study that the supply chain managers’ leadership communication style was good for they can effectively direct people to obey instructions with little or no question and to resist change, manage situations, performing within a strictly delineated framework where everything is neatly organized and structured , their level of information sharing was high for they can precisely articulate ideas, concepts and negotiations that are aligned to their work objectives in order to reach their goals, their level of performance was high for they possess a consistent, reliable, and steady communication style , the better the supply chain managers’ leadership communication style along competency, consistency, and commitment, the higher is their level of information sharing ,the better the supply chain managers leadership communication style along ccompetency, consistency, and commitment, the higher is their level of performance, and the higher the supply chain managers level of information sharing, the higher is their level of performance. Likewise, the independent variables the supply chain managers’ leadership communication styles along command/control and competency as well as their level of information sharing are the drivers of supply chain managers’ level of performance.